Identifying high-risk profile in primary antiphospholipid syndrome through cluster analysis: French multicentric cohort study. Issue 1 (9th March 2023) - Guedon, Alexis F; Ricard, Laure; Laurent, Charlotte; De Moreuil, Claire; Urbanski, Geoffrey; Deriaz, Sophie; Gerotziafas, Grigorios; Elalamy, Ismail; Audemard, Alexandra; Chasset, Francois; Alamowitch, Sonia; Sellam, Jérémie; et al.
Abstract : Introduction: Antiphospholipid syndrome (APS) is an autoimmune disease characterised by thrombosis (arterial, venous or small vessel) or obstetrical events and persistent antiphospholipid antibodies (aPL), according to the Sydney classification criteria. Many studies have performed cluster analyses among patients with primary APS and associated autoimmune disease, but none has focused solely on primary APS. We aimed to perform a cluster analysis among patients with primary APS and asymptomatic aPL carriers without any autoimmune disease, to assess prognostic value. Methods: In this multicentre French cohort study, we included all patients with persistent APS antibodies (Sydney criteria) measured between January 2012 and January 2019. We excluded all patients with systemic lupus erythematosus or other systemic autoimmune diseases. We performed hierarchical cluster analysis on the factor analysis of mixed data coordinates results with baseline patient characteristics to generate clusters. Results: We identified four clusters: cluster 1, comprising 'asymptomatic aPL carriers', with low risk of events during follow-up; cluster 2, the 'male thrombotic phenotype', with older patients and more venous thromboembolic events; cluster 3, the 'female obstetrical phenotype', with obstetrical and thrombotic events; and cluster 4, 'high-risk APS', which included younger patients with more frequent triple positivity, antinuclear antibodies, non-criteria manifestations and arterial events. Regarding survival analyses, asymptomatic aPL carriers relapsed less frequently than the others, but no other differences in terms of relapse rates or deaths were found between clusters. Conclusions: We identified four clusters among patients with primary APS, one of which was 'high-risk APS'. Clustering-based treatment strategies should be explored in future prospective studies.